High-Achieving Students’ Strategies toward E-Learning Practice during Covid-19 Pandemic - Hujah Tu’al’ Syadiah; Andri Saputra; Ali Akbarjono (Yayasan Karinosseff Muda Indonesia, 2021)
This research investigates the strategies used by high-achieving students of the English department at several colleges and their understanding of learning materials studied during the Covid-19 Pandemic. The researcher decided on a small sample size of 9 students majoring in English at several universities in Bengkulu to be sampled in this research, ranging in age 20 to 21 years old. This research employed a descriptive qualitative method to collect the research data using the interview method to answer the research questions. From the results of this study, following the focus of the proposed research, there are three kinds of strategies used by nine students in this study. The first is a note-taking strategy, the second is a reading strategy, and the third is a recording strategy. This strategy is used by students who high-achieving in the learning process to understand the material being studied.